Political Popularity and Party Support Behavior in Thai Democracy - Sudjaroen, Srunporn; Piriyawatthana, Wallop; Chaobanpho, Yaowaluk (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
This academic article aims to synthesize and analyze the political popularity of Thai citizens within a democratic framework through the lense of Political Marketing and Voting Behavior theories. It employs an integrative framework that combines structural dimensions, political culture, and the dynamic of digital media technology to explain the factor shaping public support for political parties and leaders. The article adopts a qualitative methodology, drawing upon academic literature and case studies of the 2019 and 2023 general elections in Thailand. The findings reveal that political popularity in Thailand is shaped by interrelated factors: the frequent change in the electoral system, the persistent entrenchment of patron–client political culture, and the critical role of digital media in constructing political image and mobilizing public sentiment. Moreover, the study reveals the emergence of an “emotional democracy,” in which citizens’ decisions are often driven by sentiment, image, and emotional attachment rather than rational policy evaluation. The article further proposes pathways to foster sustainable political popularity through the promotion of civic education, establishing inclusive policy platforms, and enhancing political parties’ ability to adapt to Thailand’s shifting inclusive policy context. The article’s contribution lies in its integration of structural and behavioral perspectives, offering a dynamic conceptual framework for understanding political popularity in the context of a developing democracy.